Apresentação e avaliação de aspectos clínico-epidemiológicos e histopatológicos de lesões em pacientes com Leishmaniose tegumentar americana (LTA), forma ulcerada, provenientes de áreas endêmicas da região do Cariri. 1990-2003 - Silva, Claúdio Gleidiston Lima da (2004)
American Cutaneous Leishmaniasis (ACL) is an endemic disease in the Brazil. In spite of the measures employed to the control the disease continues in expansion and with tendency to urbanization. The northeast of Brazil excels with foci of this zoonosis, especially in the mountains and foothills around Ceará state. Cariri in the south of Ceará close to plateau of Araripe that reaches 900m, bordering the states of the Pernambuco, Piauí and Paraíba is kind of this place with scarce studies. The present work evaluated the clinical and epidemiological aspects of the ACL in the Cariri, especially emphasizing study histopathologic material originating from borders of the ulcers of 64 patients with ACL. The material studied came from APACIC histopatology laboratory (1990-2003), and Pathology laboratory of the Juazeiro do Norte Medicine School (Tropical Medicine Nucleus, 2000-2003). The archived material was constituted of the patient’s records, slides and paraffin blocks. The clinical and epidemiological informations were collected in the specific protocol. The histological material was examine by microscopic routine of the HE and Giemsa, sometimes others histotecnologies techniques were performed. The results revealed Barbalha with highest number of the ACL (n=30); ACL was predominantly rural (n= 38); urbanization of the ACL in the Juazeiro do Norte; male sex (n=39), brown skin (n= 43) and farmer’s (n= 13) prevailed; the ulcerated simple form (n= 63) was most common involving mainly the legs; the nonspecific chronic inflammatory reaction with repair response prevailed in the cases of the ACL; Montenegro skin test, serology and histopathology without identification of the parasites in the absence of the clinical and epidemiological setting should not be used separately to diagnosis ACL.